Human-centered design: An approach to capacity building and co-design of inclusive tools for the Central American agricultural sector - Zapata Caldas, Emmanuel; Bonilla, Melissa; Howland, Fanny C.; Muller, Anna (Bioversity International and the International Center for Tropical Agriculture, 2023)
Blog about the implementation process of the Human Centered Design (HCD) approach in Central America, describing the general steps taken to identify the digital tools that respond to the different types of users (e.g. farmers, technicians and decision makers) with whom we work. It presents the main results of the work done in Guatemala and Honduras, and concludes with some reflections and ideas about the work to be done during 2024. Link: https://alliancebioversityciat.org/stories/human-centered-design-approach-capacity-building-and-co-design-inclusive-tools-central